The Relationship Between Hamstring Tightness and Lumbar Hyperlordosis and Trunk Flexibility in Students at Muhammadiyah University Surabaya - Ken Siwi; Nurul Romadhona; Anisha Kirana (Health & Medical Sciences, 2026)
This study aims to investigate the relationship between hamstring tightness and lumbar hyperlordosis and trunk flexibility in students at Muhammadiyah University Surabaya. The study used a quantitative approach with a cross-sectional observational study design involving 30 students with hamstring tightness disorders. Hamstring tightness was measured using the straight leg raise test, the lumbar lordosis angle was measured with a flexicurve, and trunk flexibility was measured using the fingertip to floor test. Data analysis was performed using Pearson Product Moment correlation test with a significance level of p < 0.05. The results showed a significant correlation between hamstring tightness and trunk flexibility with a p-value of 0.00 and a very strong correlation coefficient (R = 0.984), while lumbar hyperlordosis data did not show a significant correlation with trunk flexibility or hamstring tightness. The conclusion of this study confirms that hamstring shortening has a very strong relationship with limited trunk flexibility, but is not directly related to changes in the lumbar lordosis angle. These findings highlight the importance of physiotherapy interventions that focus on increasing hamstring flexibility as a preventive and functional strategy for students with high sedentary activities.